Distribution of heavy metal concentrations in Trisidos Kiyonoi: a biomonitoring concern - Chee, Kong Yap; Edward, Franklin Berandah; Wan, Hee Cheng; Kumar, Krishnan; Omar, Hishamuddin; Risandiansyah, Rio; Chee, Wah Yap; Meng, Chuan Ong (Scientific Research and Community, 2022)
Locally known bivalves “siput pulas”, Trisidos kiyonoi, were collected from kampong Panchor, Pantai Remis, Perak. The bivalves were then dissected into eight different parts of soft tissue: the remainder, muscle, mantle, byssus, foot, gills, gonads, and shell. The soft tissues were then analyzed for Cu, Cd, Zn, Pb, Ni and Fe. The byssus included the highest quantities of Cd, Cu, Fe, Pb, and Ni among the soft tissues, while the mantle contained the highest concentrations of Zn. This study suggested that byssus is a good biomonitoring organ for Cd, Cu, Fe, Pb and Ni, while shell was suggested as a good biomonitoring tool for Cd, Pb and Ni. This biomonitoring information on the metal distribution in T. kiyonoi is vital for future reference.